Childhood to Early-Midlife Systolic Blood Pressure Trajectories: Early-Life Predictors, Effect Modifiers, and Adult Cardiovascular Outcomes. Issue 6 (December 2015) - Theodore, Reremoana F.; Broadbent, Jonathan; Nagin, Daniel; Ambler, Antony; Hogan, Sean; Ramrakha, Sandhya; Cutfield, Wayne; Williams, Michael J.A.; Harrington, HonaLee; Moffitt, Terrie E.; Caspi, Avshalom; Milne, Barry; et al.
Abstract : Previous studies examining blood pressure change over time have modeled an average population trajectory. Recent research among older adults suggests there may be subgroups with different blood pressure trajectories. Identifying subgroups at risk of developing adult hypertension early in life can inform effective risk reduction efforts. We sought to identify different systolic blood pressure trajectories from childhood, their correlated risk factors, and early-midlife cardiovascular outcomes. Blood pressure data at ages 7, 11, 18, 26, 32, and 38 years from a longitudinal, representative birth cohort study (n=975) were used to identify 4 distinct trajectory groups via group-based trajectory modeling: normal (21.8%), high-normal (43.3%), prehypertensive (31.6%), and hypertensive (4.2%). The categories refer to blood pressure beginning at the age of 7 years and most recently measured at the age of 38 years. Family history of high blood pressure (odds ratio [OR], 43.23; 95% confidence interval [CI], 5.27–354.65), male sex (OR, 109.48; 95% CI, 26.82–446.96), being first born (OR, 2.5; 95% CI, 1.00–8.69) and low birth weight (OR, 2.79; 95% CI, 2.49–3.09) were associated with hypertensive group membership (compared with the normal group). Higher body mass index and cigarette smoking resulted in increasing blood pressure across trajectories, particularly for the higher blood pressure groups. Prehypertensive and hypertensive trajectory groups had worse cardiovascular outcomes by early midlife. Harmful blood pressure trajectories are identifiable in childhood, associated with both antecedent and modifiable risk factors over time, and predict adult cardiovascular disease risk. Early detection and subsequent targeted prevention and intervention may reduce the lifecourse burden associated with higher blood pressure. Abstract : Supplemental Digital Content is available in the text.